Genome-Wide Identification of the ABC Gene Family in Rosaceae and Its Evolution and Expression in Response to Valsa Canker - Chenglong Du; Hongqiang Yu; Huanhuan Hu; Zhiqi Dou; Cunwu Zuo; Junqiang Niu (Horticulturae)
The ATP-binding cassette (ABC) transporter family plays a critical role in plant growth, development, and disease resistance. However, the evolution and functional characteristics of the ABC gene family in Rosaceae species have not been fully studied. In this study, we performed the first whole-genome identification, as well as an evolutionary analysis and comparative analysis of ABC genes in Rosaceae plants. We identified 3037 ABC genes in 20 plant species, classifying them into eight subfamilies. Comparative analysis revealed significant variations in family size and expansion patterns among species, suggesting adaptive evolution. Tandem duplication (TD: where genes are duplicated in sequence) and whole-genome duplication (WGD: duplication of the entire genome) were identified as the primary drivers of ABC family expansion. In pears, gene pairs produced by WGD underwent purifying selection. Gene ontology (GO) enrichment analysis indicated the involvement of ABC proteins in transmembrane transport and signal transduction pathways. Under Valsa pyri infection, most ABC genes were upregulated in the early stages, highlighting the role of ABCG genes in pathogen response. A weighted gene co-expression network analysis (WGCNA) identified five key ABCG genes potentially involved in pathogen resistance regulation. Our findings provide insights into the evolutionary adaptability of the ABC gene family and their potential applications in plant disease defense.